Lead Immobilization and Hydroxamate Ligand Promoted Chloropyromorphite Dissolution. (20th July 2014) - Adam, Nadia K.
Abstract : The immobilization of lead, a major environmental contaminant, through phosphate amendments to form the sparingly soluble lead phosphate mineral chloropyromorphite [Pb5 (PO4 )3 ] (CPY) is an effective in situ strategy for soil remediation. An important question is the effect of microbial processes on this remediation. Here, we investigate the role of the microbial siderophore ligand desferrioxamine-D1 (DFO-D1 ) and its analog acetohydroxamic acid (aHA) in CPY lability using pH-dependent batch dissolution kinetics and model calculations. Both (0.01) M aHA and (0.00024) M DFO-D1 are similarly effective and enhance lead release from CPY by more than two orders of magnitude at pH > 6 compared to in the absence of ligands. This is consistent with model calculations of pH-dependent (aqueous) complexation of lead with hydroxamate ligands. More importantly, pH-dependent ligand sorption is predictive of its ligand promoted dissolution behavior. Our results suggest that organic ligands can significantly increase CPY lability at alkaline pHs in soils and sediments and that addition of P amendments to immobilize Pb as CPY may only be successful at acid pHs.